Prevalence of COVID – 19 Infection and Associated Risk Factors among Travelers at Medblue Modern Laboratories Center, Juba, South Sudan - Kutjok, PHILIP; NYICAR, SIMON (IJRDO-Journal of Applied Science, 2021)
ABSTRACTBACKGROUND: Prevalence of COVID-19 infection is a worldwide problem. The magnitude of risk factors to COVID-19 infections in South Sudan is rapidly increasing following its spread in the country. However, studies about the risk prevalence of COVID-19 infection among travelers and factors associated with of COVID-19 infection are lacking in South Sudan.OBJECTIVE: The study was conducted to estimate prevalence and associated factors with COVID-19 infection among travelers at Medblue Modern Laboratories and PCR.METHODS: A study was carried out from December 2020 to May 2021 to estimate prevalence and risk factors associated with COVID-19 infection amongtravelers at Medblue Modern Laboratories Center. In total, 58,513 travelers participated in the study. Data was analyzed using various methods.RESULTS: A total of 4,057 (38.12%) travelers had a high exposure risk of COVID-19 infection of which 2,979 (73.43%) were males and 1,078 (26.57%) were females. The most affected travelers were males between the age of 35 – 44 with 1,436 (35.40%)  long sitting hours at airports, inadequate supply of PPE, lack of access to alcohol-based hand rub, travel without being tested, and frequent travel were found to be risk factors for COVID-19 infection.CONCLUSION: Travelers face a high risk of COVID-19 infection while traveling, sitting for long  hours at airports from every airport to another, lacking physical distance and plus traveling without being tested. Proper use and adequate supply of PPE and the implementation of basic infection prevention and control with frequent protocol revision and strict supervision are crucial to limit exposure risk to COVID-19 among travelers